2021
DOI: 10.3390/cells10010076
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Targets from LRRK2 Rescue Phenotypes

Abstract: Parkinson’s disease (PD) is an age-dependent neurodegenerative condition. Leucine-rich repeat kinase 2 (LRRK2) mutations are the most frequent cause of sporadic and autosomal dominant PD. The exact role of LRRK2 protective variants (R1398H, N551K) together with a pathogenic mutant (G2019S) in aging and neurodegeneration is unknown. We generated the following myc-tagged UAS-LRRK2 transgenic Drosophila: LRRK2 (WT), N551K, R1398H, G2019S single allele, and double-mutants (N551K/G2019S or R1398H/G2019S). The prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 67 publications
1
5
0
Order By: Relevance
“… 8 , 41 , 42 , 43 A recent study has shown that both p.R1398H and p.N551K were able to counteract the putative pathogenic effects of p.G2019S in Drosophila models. 44 The literature therefore suggests that each of these variants has measurable effects on protein function in cells and in vivo that are consistent with the proposed direction of effects for risk versus protection. However, the relation between the functional impact and risk for PD needs to be further investigated for these coding variants.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“… 8 , 41 , 42 , 43 A recent study has shown that both p.R1398H and p.N551K were able to counteract the putative pathogenic effects of p.G2019S in Drosophila models. 44 The literature therefore suggests that each of these variants has measurable effects on protein function in cells and in vivo that are consistent with the proposed direction of effects for risk versus protection. However, the relation between the functional impact and risk for PD needs to be further investigated for these coding variants.…”
Section: Discussionsupporting
confidence: 52%
“…In addition, LRRK2 p.R1398H has been shown to affect GTPase and Wnt signaling activity contrary to pathogenic LRRK2 mutations 8,41‐43 . A recent study has shown that both p.R1398H and p.N551K were able to counteract the putative pathogenic effects of p.G2019S in Drosophila models 44 . The literature therefore suggests that each of these variants has measurable effects on protein function in cells and in vivo that are consistent with the proposed direction of effects for risk versus protection.…”
Section: Discussionmentioning
confidence: 57%
“…Only one transcriptomic study in Drosophila melanogaster has identified altered pathways associated with N551K, including alterations of the oxidoreductase pathway. 29 Structural analysis of full-length human LRRK2 has shown that the ANK and LRR domains interact with the kinase domain but not the ARM domain, which shows flexibility relative to the rest of the protein. 30 Rab proteins directly interact with LRRK2 via the ARM domain 31,32 but the H230R variant is not located in the potential Rab-interacting regions of this domain (residues 386-392).…”
Section: Discussionmentioning
confidence: 99%
“…Another rare variant, N551K, belonging to a protective haplotype (N551K-R1398H-K1423K) has been reported for PD patients (22,23) but the mechanisms explaining how this haplotype confers neuroprotection in PD is not clear and it has not been functionally assessed. Only one transcriptomic study in Drosophila melanogaster has identified altered pathways associated with N551K, including alterations of the oxidoreductase pathway (24). Structural analysis of full-length human LRRK2 has shown that the ANK and LRR domains interact with the kinase domain but not the ARM domain, which shows flexibility relative to the rest of the protein (25).…”
Section: Discussionmentioning
confidence: 99%